1999
DOI: 10.1076/ceyr.19.1.4.5341
|View full text |Cite
|
Sign up to set email alerts
|

Components responsible for the surface tension of human tears

Abstract: The surface tension of tears is due to a complex of tear lipocalin with a polar lipid fraction extractable from tears by lipid solvents and different from meibomian lipid. Lipocalin and this lipid fraction may be secreted together by the lacrimal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
2
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(144 citation statements)
references
References 8 publications
6
132
2
4
Order By: Relevance
“…See Section 4 for details. also reported that the equilibrium and maximal surface pressures achieved by tears from "healthy eyes" (where TF is stable for more than 15 s) is about 5 mN/m higher than the surface pressures of samples from "dry eyes" (where TF ruptures after less than 10 s) [8,28]. Again DPPC has more profound influence on max than SM, particularly in compositions with low PL amount.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…See Section 4 for details. also reported that the equilibrium and maximal surface pressures achieved by tears from "healthy eyes" (where TF is stable for more than 15 s) is about 5 mN/m higher than the surface pressures of samples from "dry eyes" (where TF ruptures after less than 10 s) [8,28]. Again DPPC has more profound influence on max than SM, particularly in compositions with low PL amount.…”
Section: Discussionmentioning
confidence: 93%
“…Both PL also increased the maximal surface pressures achieved by the pseudo-binary films during compression. The tear film lipid layer is the key compound responsible for the surface tension of the natural tears [4,5,8]. The increase of its capability to reach high surface pressures (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The polar lipids reside at the aqueous interface, while the non-polar lipids reside above. A study by Nagyová and Tiffany [21] found almost no dissolved lipid in tears extracted from human eyes, indicating that both components of the lipid layer are insoluble. The mucus layer is secreted from cells which are situated in the conjunctival epithelium.…”
Section: Introductionmentioning
confidence: 99%